(untitled) (American Journal of Arts and Human Science, 2024)
The study explores Educational Challenges Affecting Girls’ Academic Achievement in Public Secondary Schools in Burao, Somaliland. It utilizes both quantitative and qualitative research methods to gain a comprehensive understanding of the obstacles faced by girls in their educational pursuits. The study reveals that socioeconomic factors, cultural traditions, and insufficient school infrastructure significantly hinder girls’ education, with financial constraints, early marriage, and gender-biased cultural practices identified as significant barriers. The recommendations of this study, if effectively implemented, have the potential to bring about substantial positive change. These recommendations include the implementation of financial support programs, raising community awareness, improving school infrastructure, and providing career guidance and skills training.